Leukocyte Profile of Broiler Chickens (Gallus domesticus) After Consumption of Feed With Spirulina (Spirulina sp.) Feed Additives and Liquid Nano Chitosan - Gunawan, Rida Arwanda; Sunarno, Sunarno; Djaelani, Muhammad Anwar; Kasiyati, Kasiyati (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Broilers (Gallus domesticus) are prone to stress and immune suppression due to inadequate environmental conditions and feed quality. Spirulina, known for its antioxidant and immunostimulant properties, and liquid nano chitosan, which has antibacterial activity, are considered promising feed additives for broiler health. This study aimed to evaluate the effects of Spirulina flour, liquid nano chitosan, and their interaction on broiler leukocyte profiles. A factorial completely randomized design was used, with six treatment groups and four replications. Treatments included a control and diets supplemented with 0; 3; or 6% Spirulina powder, combined with 0 or 5% liquid nanochitosan. The treatments were applied for 26 days. Leukocyte observations were performed using Giemsa-stained blood smears at 400× magnification. Data were analyzed using Two-Way ANOVA (α= 0.05) and the Friedman Test. Results showed normal leukocyte morphology. Spirulina supplementation had no significant effect (P >0.05) on leukocyte, heterophil, or lymphocyte counts. In contrast, 5% liquid nano chitosan significantly affected (P <0.05) leukocyte and lymphocyte numbers. No interaction between the two additives was observed. In conclusion, Spirulina (3–6%) showed potential as a feed additive, while 5% liquid nano chitosan reduced leukocyte and lymphocyte counts. These natural additives may support broiler health without altering leukocyte profiles.